The Influence Of Product Quality, Price Perception And Brand Ambassadors On The Repurchase Interest Of Aloe Vera Nature Republic Products On NCT 127's Fanbase On Social Media Twitter - Herawati, Amelia Putri; Elwisam; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine Product Quality, Price Perception, and Brand Ambassador regarding Nature Republic's Aloe Vera Product Repurchase Interest in NCT 127 Fanbase on Twitter Social Media. This data uses primary data in the form of a questionnaire distributed to consumers who have used aloe vera nature republic products to 100 respondents, using the purposive sampling method. Using purposive sampling techniques, samples are expected to be by the requirements or criteria needed in this study. The data used is primary data by distributing questionnaires. Data analysis techniques using the SmartPLS program. Results were found after data processing analysis with the following conclusions: product quality, price perception, and brand ambassadors positively and significantly affect repurchase interest. It has previously been tested against question items that were declared valid as well as reliable